Online grooming Sebagai Awal Eksploitasi Seksual pada Anak: A Systematic Literature Review - Dona Suzana; Allifa Najla Widiyanti; Sunny Yohana (Journal of Innovative and Creativity, 2025)
The proliferation of technology and social media has made cybercrime increasingly widespread. One of the kind called online grooming was defined as a process or condition in which adults manipulate minors as an approach to trust and obedience that leads to sexual behavior. According to some studies, the minors victimized online groming are not aware that they are being prepared sexually and make it seem to be a conversation or flirting because of the methods and strategies employed by the anonymers or groomers in the process of getting closer to the victim. The study uses systematic literature review (SLR) or systematic literacy review to identify dangers caused by online materials by referral articles, journals and other literature sources obtained through databases.